Utilization of Maternal Health Care Services in Slum Areas of Kathmandu Valley, Nepal - Bijaya Mani Devkota; Tantrika Raj Khanal; Bhakti Prasad Subedi; Indira Pant (Journal of Development and Administrative Studies, 2025)
This study aims to investigate on the factors affecting the utilization of maternal services surrounding maternal health practices in those demolished areas in the Kathmandu valley with socio-cultural norms that heavily shape the scope of these services. The study cultivated the essence of women in search of maternal health services, like ANC, skilled birth attendance, and postnatal care, and some challenges faced by healthcare providers while ensuring maternal healthcare services. A qualitative study was conducted, including in-depth interviews and focus group discussions among reproductive aged women and healthcare providers as well as important community stakeholders. The study highlights the improvements in awareness about maternity health services because of government and non-governmental organizations' involvements; however, many still face challenges. These challenges include financial constraints, lack of health facilities, poorly maintained roads access, lack of skilled health personnel, and other crucial life aids in maternal health care. Socio-cultural beliefs, which encompass traditional healing practices influence maternal health-seeking behaviors; some women have delayed or avoided formal healthcare services as a result. Increased male involvement in maternal health, community-based support programs, and female community health volunteers (FCHVs) would help improve healthcare utilization. The structural aspects of healthcare systems have to be improved. The strengthening of maternal services, ensuring a supplementary source of finance for maternal services, improving access to transport should certainly be considered. Health education programs aimed at challenging cultural practices are seriously needed if improvement in health access and quality lies beyond. The co-operation among the state, local government bodies, and NGOs is requirement. Targeted interventions would serve in either reducing or completely eliminating some of these forms of disparities in maternal health. The result is a healthier future for mothers and their families in squatter areas of Kathmandu Valley.